(untitled) (Eurasian Journal of Philology Science and Education, 2020)
The article discusses the features of linguistic and religious consciousness and their unity in the worldview of mankind. Religion as a special form of worldview and worldview is one of the integral components of culture. Religion forms a special way of perception, the moral consciousness of a people, their spiritual national view of the surrounding reality, which add up to a kind of religious picture of the world. Religious and linguistic consciousness is a form of social consciousness, which is characterized by dynamism and evolves during the development of man and society. Any answer to the question about the structure and nature of the world is based on a person’s experience, facts that he fixes both by sensory organs and devices, their amplifiers, and on the correlation of these facts with a cognitive (thought) model or theory. Faith is a very important concept in human life. It applies to a wider context than the religious domain alone. This concept touches on the extremely deep foundations of human life, the meanings that form it. Recognizing the existing role of religious consciousness in the life of mankind, as well as analyzing religious words, one can determine the national values and consciousness of the people. The basis of religious consciousness is a person’s belief in the supernatural, which serves as a criterion that reveals the essence of language and religion.